2022
DOI: 10.5194/isprs-archives-xliii-b2-2022-845-2022
|View full text |Cite
|
Sign up to set email alerts
|

3d Models and Non-Destructive Investigations: Towards a Meeting in Digital Twins

Abstract: Abstract. The digitisation projects of architectural heritage are a field of research continuously evolving and updating in parallel to technological innovations that allow to progressively boost the challenges and requirements of geometric and semantic richness of the related digital configuration of results. Among the arduous tasks under observation, there is the increasing need to harmonize and make the spatial and heterogenous information aspects cooperating. This paper focuses on the procedures for struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In fact, this increasingly popular technology has demonstrated that the informative models derived from reality-based data-such as point clouds, 3D mesh, orthophotos and archival sourcesnot only need to be used as standalone data, they can be merged in an HBIM to provide a powerful tool for heritage experts. Such an information system allows the management of multi-disciplinary analyses of the considered buildings [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, this increasingly popular technology has demonstrated that the informative models derived from reality-based data-such as point clouds, 3D mesh, orthophotos and archival sourcesnot only need to be used as standalone data, they can be merged in an HBIM to provide a powerful tool for heritage experts. Such an information system allows the management of multi-disciplinary analyses of the considered buildings [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…If it is ascertained that many aspects of the reality-based techniques that we now consider traditional are largely established, and since the automation imprinted by the SfM (structure from motion) techniques [ 13 , 14 ] have allowed for the photogrammetric techniques to be able to supply point clouds substantially similar to the LiDAR (light detection and ranging) ones, attention can now be moved to the innovation of processing processes, which often include optimizing hybrid systems and allowing for obtaining multi-sensor and multi-content surface models [ 15 , 16 ].…”
Section: Multi-sensor 3d Survey and Mapping For Ch Metric Documentationmentioning
confidence: 99%
“…Sharing digital twins of monuments or CH sites with a wider audience opens several opportunities in different areas, ranging from geomatics to urban planning, but also to tourism and architecture. Indeed, the accessible accurate 3D model of an ancient building with data in the form of pointclouds and 3D triangulated meshes provides essential information for studying adequate restoration measures, making it possible to adopt Building Information Modelling (BIM) standards (Dursun et al 2022, Patrucco et al, 2022. Moreover, this data can be further enriched through the application of state-of-the-art machine and deep learning algorithms that allow for first identifying critical structural components and then evaluate the need of targeted interventions , Matrone et al, 2020.…”
Section: Introductionmentioning
confidence: 99%